Post-smolt survival of Baltic salmon in context to changing environmental conditions and predators - Friedland, Kevin D.; Dannewitz, Johan; Romakkaniemi, Atso; Palm, Stefan; Pulkkinen, Henni; Pakarinen, Tapani; Oeberst, Rainer (ICES Journal of Marine Science, 2016)
The survival of Baltic salmon Salmo salar during the first year at sea (post-smolt stage) has declined since the beginning of the 1990s. In this analysis, we complement previous studies on possible causes of this decline by considering a suite of environmental parameters, potential change in predation pressure, and post-smolt growth. Marine survival estimates were found to be negatively correlated with temperature, indicating that warming conditions have not favoured survival. Survival was also found to be positively correlated with dissolved oxygen levels and regionally related to shifts in salinity. These relationships were further studied in context to the potential predation on post-smolts by one of the main piscivores in the Baltic, Eastern Baltic cod (Gadus morhua callarias). Concomitant with changes in environmental conditions, Baltic cod has changed its latitudinal range, moving northward in the Baltic, possibly in response to warming conditions. These changes lead us to hypothesize that predation pressure on salmon may have increased in recent years as cod has now occupied habitats used by salmon post-smolts during their southward feeding migrations. This predation may have been intensified as a result of anoxic conditions in the central basin by concentrating predation interactions in coastal waters and/or the upper water column typically occupied by salmon post-smolts. Indicators of post-smolt growth were applied to test the alternate hypothesis that mortality is growth-mediated; these indicators lacked a time series trend, which supports the contention that shifting predation pressure rather than feeding opportunities is responsible for the decline in post-smolt survival in Baltic salmon.